KOMBINASI ULTRASOUND DAN DRY NEEDLING LEBIH MENURUNKAN DISABILITAS LEHER DARI PADA KOMBINASI ULTRASOUND DAN HOLD RELAX PADA MYOFASCIAL PAIN SYNDROM OTOT UPPER TRAPEZIUS - Santoso, Iman; Satriyasa, Bagus Komang; Munawaroh, Muthiah; Sandi, I Nengah; Muliarta, Made; -, Wahyuddin (Sport and Fitness Journal; Volume 6, No.2, Mei 2018, 2018)
Introduction : Upper trapezius myofascial pain syndrom (MPS) is characterized by presence of trigger points in upper trapezius muscle. MPS can cause disability and also has negative economic effect. Purpose : The reserach’s goal is to improve that combination of ultrasound and dry needling was better than combination of ultrasound and hold relax to decrease neck disability index. Methods : This research used experimental methods to study with pre-test and post-test control group design. Number of samples of the experimental group was 17 subjects given three times treatment of combination of ultrasound and dry needling, while in the control group were 17 subjects given three time treatment of combination of ultrasound and hold relax. NDI was used as out come measure. Shaphiro-wilk test was used to test the normality and levene’s test was used to test the homogenity. wilcoxon signed ranked test was used for hipothesis I, t-test related was used for hipothesis II and t-test independent wa used for hipothesis III. Results : The research showed that: (1) There was significant decrease of NDI in the experimental group . values of mean for pre test were 42,04 + 7,33 % and post test were 10,18 + 3,78 %. with p value = 0.000 (p <0.05) (2) there was significant decrease of NDI in the control group. values of mean for pre test were 45,29 + 6,03 % and post test were 22,24 + 5,42 %, with p value = 0.000 (p <0.05) (3) There were significant differences between experimental group and control group comparing with the differences of post test values between the group. The mean of post test values in experimental group showed 10,18 + 3,78 % meanwhile 22,24 + 5,42% in control group, with p value = 0.000 (p <0.05). Conclution : It was concluded that combination of ultrasound and dry needling and combination of ultrasound and hold relax can decrease the neck disability index. Combination of ultrasound and dry needling was better than combination of ultrasound and hold relax to decrease neck disability index in subject with upper trapezius myofascial pain syndrom.